Pancreatic family history does not predict disease progression but connotes alcohol consumption in adolescents and young adults with acute pancreatitis: Analysis of an international cohort of 2,335 patients - Juhász, Márk Félix; Farkas, Nelli; Szentesi, Andrea; Wedrychowicz, Andrzej; Nita, Andreia Florina; Lásztity, Natália; Tészás, Alexandra; Tokodi, István; Vincze, Áron; Eross, Bálint; Izbéki, Ferenc; Czakó, László; et al. (Frontiers in Medicine, 2022)
Background: In pediatric acute pancreatitis (AP) a family history of pancreatic diseases is prognostic for earlier onset of recurrent AP (ARP) and chronic pancreatitis (CP). No evidence supports the same association in adult-onset pancreatitis. Age-specific reasons of familial aggregation are also unclear. We aimed to examine the prognostic role of pancreatic family history for ARP/CP and observe possible underlying mechanisms. Methods: We conducted a secondary analysis of the Hungarian Pancreatic Study Group’s (HPSG) multicenter, international, prospective registry of AP patients, both children and adults. We compared positive and negative family history of pancreatic diseases, in different age groups, and analyzed trends of accompanying factors. Chi-square and Fisher exact tests were used. Results: We found a higher rate of ARP/CP in the positive pancreatic family history group (33.7% vs 25.9%, p=0.018), peaking at 6-17 years. Idiopathic AP peaked in childhood in the positive family history group (75% 0-5 years) and was consistently 20-35% in the negative group. A higher rate of alcohol consumption/smoking was found in the positive groups at 12-17 years (62.5% vs 15.8%, p=0.013) and 18-29 years (90.9% vs 58.1%, p=0.049). The prevalence of diabetes and hyperlipidemia steadily rose with age in both groups. Conclusion: Positive family history most likely signifies genetic background in early childhood. During adolescence and early adulthood, alcohol consumption and smoking emerges – clinicians should be aware and turn to intervention in such cases. Contrary to current viewpoints positive pancreatic family history is not a prognostic factor for ARP and CP in adults, so it should not be regarded that way.